Smart Cities Marketing and Its Conceptual Grounds - Maček, Anita; Ovin, Rasto; Starc – Peceny, Urška (Naše gospodarstvo/Our economy, 2019)
The most frequent definition of the smart city in the literature defines it as a developed urban area that creates sustainable economic development and high quality of life. Therefore, a city should always be capable of identifying and effectively resolving its key development challenges in order to improve the quality of life of its citizens. Regarding economics approach, the authors rely on endogenous growth theory derived from Arrow. The authors explore the role of smart city management and governance, which will have to combine the need for capital with the need to ensure the environment that this capital will enhance modern urban producing factors. Hence, the authors discuss communication aspects and the importance of the evolution toward smart communities, where the idea is not on making places smart anymore, but rather focus on humans and their needs. For an emerging smart city, market built up of smaller cities and municipalities describes the changing role of marketing and the shift of roles in its processes in order to show the urge to become familiar with the spirit of open innovation and rethink marketing strategy in this emerging reality.